An Open Label Pilot Study of a Brief Psychosocial Intervention for Disaster and Trauma Survivors - O'Donnell, Meaghan Louise; Lau, Winnie; Fredrickson, Julia; Gibson, Kari; Bryant, Richard Allan; Bisson, Jonathan; Burke, Susie; Busuttil, Walter; Coghlan, Andrew; Creamer, Mark; Gray, Debbie; Greenberg, Neil; et al. (Frontiers in Psychiatry, 2020)
Background: In the aftermath of disaster, a large proportion of people will develop psychosocial difficulties that impair recovery, but for which presentations do not meet threshold criteria for disorder. Although these adjustment problems can cause high distress and impairment, and often have a trajectory towards mental health disorder, few evidence-based interventions are available to facilitate recovery. Objective: This paper describes the development and pilot testing of an internationally developed, brief, and scalable psychosocial intervention that targets distress and poor adjustment following disaster and trauma. Method: The Skills fOr Life Adjustment and Resilience (SOLAR) program was developed by an international collaboration of trauma and disaster mental health experts through an iterative expert consensus process. The resulting five session, skills-based intervention, deliverable by community-based or frontline health or disaster workers with little or no formal mental health training (known as coaches), was piloted with 15 Australian bushfire survivors using a pre-post with follow up, mixed-methods design study. Results: Findings from this pilot demonstrated that the SOLAR program was safe and feasible for non-mental health frontline workers (coaches) to deliver locally after two days of training. Participants’ attendance rates and feedback about the program indicated that the program was highly acceptable. Pre-post quantitative analysis demonstrated reductions in psychological distress, posttraumatic stress symptoms, and impairment. Conclusions: This study provides preliminary evidence that the delivery of the SOLAR program after disaster by trained, frontline workers with little or no mental health experience is feasible, acceptable, safe, and beneficial in reducing psychological symptoms and impairment among disaster survivors. Randomised controlled trials of the SOLAR program are required to advance evidence of its efficacy.